Acute toxicity and antidiabetic activity of Asystacia gangetica leaf ethanol extract. Issue 1 (28th August 2019) - Ezembu, Eunice Ngozi; Okolo, Chioke Amaefuna; Obiegbuna, James; Ikeogu, Florence Chika
Abstract : Purpose: The purpose of this study is to examine the acute toxicity and antidiabetic activity of Asystacia gangetica leaf ethanol extract. Design/methodology/approach: The study was designed as completely randomized in vivo experimental model. Where acute toxicity study was carried out using 30 albino mice, randomly assigned into six groups of five mice each. Toxicity signs and mortality were observed in the rats within a period of 24 h. The acute and sub-acute antidiabetic study was carried out using 50 rats, randomly assigned into five groups of 10 rats each. The rats' blood glucose levels were determined and used to assess the acute and sub-acute antidiabetic activity of the extract. Findings: Results obtained from the acute toxicity study indicated no death in any of the study groups, even at 5, 000 mg/kg body weight and showed no signs of toxicity. The acute antidiabetic study showed that treatment with 400 mg/kg of the extract significantly ( p = 0.01) lowered glucose level in the diabetic rats from 430.6 to 177.4 mg/dl while 800 mg/kg brought down glucose level from 370 to 144.2 mg/dl by the end of 6 h following administration when compared with the diabetic control group. It was observed that the effect of the extract mostly at 800 mg/kg also compared favorably with that of the standard drug (glibenclamide), which lowered glucose level in diabetic rats from 374.2 to 176.4 mg/dl. Furthermore, the significant reduction was evident from 4, 2 and 2 h for 400 mg/kg extract, 800 mg/kg extract and 5 mg/kg glibenclamide, respectively. At sub-acute level the blood glucose was lowered from 155.6 to 127.2 mg/dl, 137 to 124.4 mg/dl and 151.8 to 121.8 mg/dl for diabetic rats treated with 400 mg/kg, 800 mg/kg and 5 mg/kg glibenclamide, respectively, when compared to the diabetic untreated rats, which ranged from 417.6 to 358.6 mg/dl. The biochemical profile, lipid profile and hematological examination were all positively restored near to normal with the herbal treatment at the different doses. At histopathology level, the liver of the rats treated with 400 mg/kg had moderate portal inflammation without interface or lobular hepatitis while that of 800 mg/kg showed severe portal inflammation with the interface and lobular hepatitis with extensive confluents necrosis. The pancreatic cells of the treated rat showed no significant difference in the β -cells of the islets of Langerhans with hyperplasia of the acinar cell when compared to the diabetic untreated. Research limitations/implications: The record of no death and signs of toxicity implies that the extract is safe for consumption even at a high dosage of 5, 000 mg/kg body weight. The significant ( p = 0.01) reduction in the plasma glucose level of the treated rats as compared to the control is an indication of blood glucose-lowering potential of the extract at two different doses. The significant reduction evident of the extract at different hours and days for the two doses implies that the extract rate of lowering potentials is dose-dependent. The evidence of moderate-severe portal inflammation with the interface and lobular hepatitis at 800 mg/kg treatment is an indication that the intake of this herb at high dosage for long period is not safe for the liver tissue. Practical implications: The outcome of this study suggested that the Asystacia gangetica should also be used as a vegetable in-home food preparation and food processing to use its antidiabetic effect. The herbal extract could also be incorporated into a food product and processed into herbal tea bag for convenient. The subjection of this herbal plant to heat treatment during processing could be a possible avenue to make it safe. Social implications: The economic burden and complications of diabetes mellitus management will be reduced if the practical implication of this research finding is implemented in foods as vegetable and in functional food production. Originality/value: This study revealed that Asystacia gangetica leaf extract may be safe and effective for use at a low dose for acute management of diabetes mellitus. This research may be of value to those living with diabetes mellitus.